Randomized trial of Tibetan yoga in patients with breast cancer undergoing chemotherapy. Issue 1 (20th September 2017) - Chaoul, Alejandro; Milbury, Kathrin; Spelman, Amy; Basen‐Engquist, Karen; Hall, Martica H.; Wei, Qi; Shih, Ya‐Chen Tina; Arun, Banu; Valero, Vicente; Perkins, George H.; Babiera, Gildy V.; Wangyal, Tenzin; et al.
Abstract : BACKGROUND: The current randomized trial examined the effects of a Tibetan yoga program (TYP) versus a stretching program (STP) and usual care (UC) on sleep and fatigue in women with breast cancer who were undergoing chemotherapy. METHODS: Women with stage (American Joint Committee on Cancer (AJCC) TNM) I to III breast cancer who were undergoing chemotherapy were randomized to TYP (74 women), STP (68 women), or UC (85 women). Participants in the TYP and STP groups participated in 4 sessions during chemotherapy, followed by 3 booster sessions over the subsequent 6 months, and were encouraged to practice at home. Self‐report measures of sleep disturbances (Pittsburgh Sleep Quality Index), fatigue (Brief Fatigue Inventory), and actigraphy were collected at baseline; 1 week after treatment; and at 3, 6, and 12 months. RESULTS: There were no group differences noted in total sleep disturbances or fatigue levels over time. However, patients in the TYP group reported fewer daily disturbances 1 week after treatment compared with those in the STP (difference, ‐0.43; 95% confidence interval [95% CI], ‐0.82 to ‐0.04 [ P = .03]) and UC (difference, ‐0.41; 95% CI, ‐0.77 to ‐0.05 [ P = .02]) groups. Group differences at the other time points were maintained for TYP versus STP. Actigraphy data revealed greater minutes awake after sleep onset for patients in the STP group 1 week after treatment versus those in the TYP (difference, 15.36; 95% CI, 7.25‐23.48 [ P = .0003]) and UC (difference, 14.48; 95% CI, 7.09‐21.87 [ P = .0002]) groups. Patients in the TYP group who practiced at least 2 times a week during follow‐up reported better Pittsburgh Sleep Quality Index and actigraphy outcomes at 3 months and 6 months after treatment compared with those who did not and better outcomes compared with those in the UC group. CONCLUSIONS: Participating in TYP during chemotherapy resulted in modest short‐term benefits in sleep quality, with long‐term benefits emerging over time for those who practiced TYP at least 2 times a week. Cancer 2018;124:36‐45 . © 2017 American Cancer Society . Abstract : The current study examines the effects of a Tibetan yoga program versus a stretching program or usual care on sleep disturbances and fatigue in women with early breast cancer who are undergoing chemotherapy. Tibetan yoga appears to be associated with fewer daily sleep disturbances, but no group differences were noted with regard to overall sleep disturbances or fatigue. Patients who practiced Tibetan yoga at least twice weekly during the follow‐up reported lower subjective and objective sleep disturbances at 3 months and 6 months after treatment compared with those who did not, and had better outcomes than those patients receiving usual care.